Serials Cataloging Handbook: An Illustrative Guide to the Use of Aacr2R and Lc Rule Interpretations - Liheng, Carol (American Library Association, 2012)
This serious tome is a no-nonsense manual, with a half-page devoted to acknowledgments and a paragraph of the introduction to the first edition (1989)